1998
DOI: 10.1002/(sici)1520-6556(1998)27:1<84::aid-htj7>3.3.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer in channel flow around a rectangular cylinder

Abstract: Heat transfer and flow visualization experiments have been made in a channel with a rectangular cylindrical section having various width-to-height ratios. Vortices were observed to shed periodically from the cylinder and then reattach to the channel wall. This reattachment of the vortices induces a periodic fluctuation in heat flux at the wall and enhances the heat transfer in the downstream region of the cylinder. The streamwise position of the maximum Nusselt number moves downstream with decreasing width-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The same Strouhal number can be seen for present work and the references [2,3,5] according to table 1. Figure 9 shows the U spectra at locations x * = 2 and 3.5 for two y plane in the wake of a square cylinder at Reynolds number of 8600.…”
Section: Spectral Analysis Of Wake Flowmentioning
confidence: 79%
See 3 more Smart Citations
“…The same Strouhal number can be seen for present work and the references [2,3,5] according to table 1. Figure 9 shows the U spectra at locations x * = 2 and 3.5 for two y plane in the wake of a square cylinder at Reynolds number of 8600.…”
Section: Spectral Analysis Of Wake Flowmentioning
confidence: 79%
“…Their experimental results showed a relationship between the flow topology and the turbulence distribution. Yao et al [4] and Nakagava et al [5] confirmed that the periodically shed vortices from the cylinder enhance the heat transfer at the downstream channel wall. A simultaneous measurement of the velocity and temperature fluctuation using the hot and cold wires was conducted by Yao et al [4] .…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…There is a large variety of bluff bodies shapes and surface configurations which have been studied experimentally [18][19][20][21][22][23][24][25] or by and using numerical simulation methods [25,26]. The main task in such studies is to reveal the effect of the cross-section area reduction ratio, the flow structure, and consequently their effects on the fuel mixing process.…”
Section: State-of-the-art: a Brief Overviewmentioning
confidence: 99%